Industry expert directors - Drobetz, Wolfgang; von Meyerinck, Felix; Oesch, David; Schmid, Markus (Journal of Banking & Finance, 2018)
We analyze the valuation effect of board industry experience and channels through which industry experience of outside directors relates to firm value. Our analysis shows that firms with more experienced outside directors are valued at a premium compared to firms with less experienced outside directors. Additional analyses, including a quasi-experimental setting based on director deaths, mitigate endogeneity concerns. The association between having directors with more industry experience and higher firm value is more pronounced for firms with larger investment programs, larger cash reserves, and during crises. In contrast, it is weaker in more dynamic industries, i.e., industries that rank high in terms of sales growth, R&D expenditures, merger activities, competitive threat, and product market changes, where the value of previously acquired experience is likely to be diminished. Overall, our findings are consistent with board industry experience being a valuable corporate governance mechanism.